Poorly differentiated thyroid carcinoma - Sushama Guruwale; Tushar Kambale; Banyameen M Iqbal; Atul Jain (Medical Journal of Dr. D.Y. Patil University, 2015)
Poorly differentiated thyroid carcinoma is rare and distinctive due to it′s a characteristic uniform cells and sometimes insular architectural pattern. These tumors are aggressive and often lethal type of thyroid tumors often has a rapid and fatal outcome despite appropriate treatment. Here we are presenting a case of a 50 yrs old woman with anterior neck swelling more on right side since five years and increasing in size for the last three months.